Hak Masyarakat Adat Atas Tenurial dalam Kerangka REDD - Dominikus Rato (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2021)
ABSTRACT: The international debate regarding the appropriate institutional and financial formulas and mechanisms in the framework of REDD+, SMF and enhancement of forest carbon stocks in developing countries continues. REDD+ is a concept of reducing greenhouse gas emissions caused by the conversion of forest functions to non-forestry, massive deforestation, resulting in a decrease in the quantity and quality of forests in developing countries, especially rainforest countries such as Indonesia, Brazil, Malaysia, which impact on decreasing the quality and quantity of O2. Indonesia has become an active player in the project. However, in the midst of this debate, the issue of certainty over tenurial rights over land and forest resources for indigenous peoples is still marginalized. This study was conducted using a socio-legal approach to protected forest communities in Alas Purwo - Banyuwangi, East Java. With the theories of social sciences, ecology, and customary law, it is found that indigenous peoples who depend on the forest, namely the people who live around the forest, consider that the forest is not only a source of livelihood, but also as a habitat in which they forming communities and civilizations. However, there is a single view that forests are a source of wealth economically. Therefore, forests as a source of regional economy through regional autonomy and increased local revenue continue to be exploited without paying attention to the tenure rights of indigenous peoples. That is the source of the conflict which becomes a time bomb with a devastating explosion if social, cultural and political communication is not immediately carried out to understand the mindset of indigenous peoples and reduce excessive forest exploitation. Finally, it was suggested that discussion of the rights of indigenous peoples living in rainforests should also discuss legal, economic and political protection. KEYWORDS: Indigenous Peoples, Tenurial Rights, REDD+.